Generations in Black and White : Photographs from the James Weldon Johnson Memorial Collection - Van Vechten, Carl, 1880-1964; Byrd, Rudolph P. (Book collections on Project MUSE., 1993)
Eighty-three photographs presenting W.E.B. DuBois, Langston Hughes, Bessie Smith, Ruby Dee, Lena Horne, James Baldwin, and others, demonstrate Van Vechten's intent to enlighten white America about black culture.